Preparation of activated charcoal adsorbent from waste tire - Barai, Drona Raj; Jha, Vinay Kumar (Scientific World, 2012)
Activated carbons were prepared from waste tire in two different routes. Some physical properties of thus prepared activated carbons were measured and the characterization of their phases was done by XRD measurement. The adsorption isotherms of methylene blue were simulated by the Langmuir and Freundlich isotherms. The Langmuir isotherms were found to have better fitting with Qmax values 0.227, 0.255 and 0.256 mmol/g for the activated carbons prepared in air, nitrogen, nitrogen and steam respectively while it was 0.275 mmol/g for activated carbon impregnated with H3 PO4 . The overall reaction was found to be pseudo-second order with the rate constant of 8.314 × 10-4 Lg/(mmolmin). The surface area of the best prepared activated carbon was 334.2 m2 /g. Scientific World, Vol. 10, No. 10, July 2012 p80-83 DOI: http://dx.doi.org/10.3126/sw.v10i10.6868